Pemanfaatan Digital Marketing Bagi Pengembangan UMKM Sektor Souvenir di Kota Surakarta - Annisa Riyu Mezaluna; Amadea Novita Mahastri; Muhammad Ilyas Bahtiar; Bayu Aji Santoso; Denisa Eka; Marjam Desma Rahadhini (Peneliti.net, 2023)
This study aims to analyze alternative strategies for UMKM development in the souvenir sector in Surakarta using SWOT analysis. This research design uses a qualitative design. Data collection techniques used are interviews with owners, employees, and administration. The results of this research show an alternative strategy for UMKM development with strengths, weaknesses, threats and opportunities. The results of the SWOT analysis produce 6 alternative strategies that can be chosen by the company, namely: 1) Establishing cooperation with potential raw material providers to increase production and market share. 2) Utilizing the convenience of Micro and Small business permits from the government to increase production and share. 3) Creating products with more varied shapes and materials 4) Implementing a management system for the craftsman's internal organization. 5) Increasing product distribution to potential areas accompanied by vigorous and continuous promotional activities by utilizing Information Technology. 6) Build and develop cooperation with parties who provide capital and product design to increase production and market share.